State regulation of agriculture in Kazakhstan within the framework of the Eurasian Economic Union (EAEU) - Zhiyentayev, S.; Dosmukhamedova , Z. (BUKETOV BUSINESS REVIEW, 2019)
State regulation of agricultural production of any country, including Kazakhstan, in modern conditions is and will be quite a relevant topic. The aim of the article is the theoretical substantiation of this thesis and its confirmation by the example of the agricultural production of Kazakhstan. In this case, it is necessary to take into account the peculiarities of the agrarian production itself when Kazakhstan joins the world economic community as an independent state. In modern conditions, competition in the EAEU is increasing, which provides an objective basis for considering the state regulation of the agricultural sector. When writing the article, the method of scientific abstraction, the method of comparative analysis, as well as other research methods that made it possible to identify the need for state regulation of agricultural production, were used. A retrospective analysis of the agrarian production of Kazakhstan was carried out, contradictions that persist as part of the development and implementation of a Single agrarian policy of the EAEU countries were identified, and proposals were made to resolve these contradictions. The results of the work will ensure adequate efficiency in the implementation of agricultural support programs for the country, and the implementation of the principles of protectionist agricultural production policies in Kazakhstan will create the agro-economic basis of its food security.